Design of a five-bar linkage for an automated power window. (2022) - Das, Angana; Mishra, Ruby; Kumar, Kartik
Abstract: Recently designed passenger vehicles with heightened features are entering the market every year. One of them is the power window which enables the fast movement of window-panes. Not opening of window-pane in an emergency is responsible for the death of passengers in some cases. Deaths of children, the disabled or older person have been reported due to carbon monoxide(CO) poisoning. Simultaneously, they were allowed to stay inside a static, locked car in the absence of other assisting occupants. Fatal injuries have also been reported repeatedly due to the sinking of the vehicle in a water body. In this paper, the design of an automatic opening mechanism is discussed for a car window during such crises. In this system, the temperature sensor, Carbon-monoxide sensor and water pressure sensor are placed inside a car cabin to monitor the temperature range, CO levels and water pressure continuously. In case of high internal temperatures or raised carbon monoxide in the cabin due to incomplete fuel combustion or excessive heat or vehicle rested under the Sun for long, or if the vehicle is subjected to pressure by flowing or static water, the sensors send signals to the motor controlling power window to slide it down. It also sends a warning message to the registered mobile phone of the vehicle owner.